ELITE : IEM-SAFE UNIMAS STUDENT SECTION E-MAGAZINE 2020/2021 - Siti Noor Linda, Taib; Ervina, Junaidi; Kasumawati, Lias (UNIMAS, 2021)
IEM-SAFE ELITE Magazine presents the activities organized by the IEM-SAFE UNIMAS Student Section. This is the first magazine by the IEM-SAFE UNIMAS Student Section. It consists of the information on the activities conducted by the IEM-SAFE UNIMAS Student Section.